Evaluating the impact of land tenure and titling on access to credit in Uganda - Petracco, Carly; Pender, John L. (International Food Policy Research Institute, 2009)
The theorized impact of land tenure and titling on access to credit has produced mixed results in the empirical literature. Land tenure and titling is hypothesized to increase access to credit because of the enhanced land security provided and the newfound ability to use land as collateral. Using land as collateral and obtaining access to credit are paramount concerns in Uganda and in all of Africa, as greater emphasis is placed on the need to modernize the agricultural system. This paper uses a new approach in evaluating whether land tenure and titling have an impact on access to credit for rural households in Uganda. The new approach includes comparisons across four categories: (1) households who have customary land with versus without a customary certificate, (2) households who have freehold land with versus without a title, (3) households with a title or certificate having freehold versus customary tenure, and (4) households without a title or certificate having freehold versus customary tenure. Each comparison is then evaluated for the impact on access to any form of credit, formal credit, and informal credit. This analysis allows for an in-depth look into which element, tenure or title, is impacting access to credit and to which type of credit, formal or informal. To conduct this analysis, matching techniques are used, including propensity score matching and the Abadie and Imbens matching method. These two methods contain both strengths and weaknesses that allow the results to support to one another. The only significant finding of the matching was a positive impact on access to credit of freehold without title over customary without certificate. Results imply that tenure, not title, impacts credit access for rural households in Uganda.--Authors' Abstract